Formation of Korean Pronunciation Skills of Uzbek Speakers (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Pronunciation is one of the most important aspects of learning a foreign language. Because the level of mastery of a language is shown through communication in that language. The main foundation of communication is the formation of pronunciation skills. Therefore, in this article, Uzbek students and teachers of the Korean language, who are learning korean, have ideas about how to master the pronunciation rules of the Korean language and how to use them in the process of conversation.